PENGEMBANGAN BUSANA BERSILUET H DENGAN HIASAN 3D - Faida Suci Wulandari; Sugiyem Sugiyem (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
The purpose of this study was to develop party wear and find out the preferences of female consumers on H silhouette party dresses with 3D sequin decorations. This research is a Research & Development research. This study uses the 4D Thiagarajan development model, namely: define, design, development, and dissemination. The data collection method in this study was an online Google form questionnaire with 52 respondents. Data analysis techniques using descriptive statistics. The results of the study were: 1) The realization of an H-silhouette party dress made of satin and organza with 3D sequin decoration, 2) Consumer preference test for party dresses 90.4% were very interested in the 3D form of decoration on party clothes, 87.7% of respondents were interested in the placement decoration, 83% of respondents were interested in the choice of satin and organza, 82.7% of respondents were interested in the H silhouette of party dresses, and 81.5% of respondents were interested in the use of white bones in party dresses.